A democracia e o Progestão: formação continuada em serviço - Obeid, Nidal Afif (2012)
The objectof this researchis thecontinuing education programforschool managers, taught in the distance, Progest o. Analyzethe extent to whichthis programentailedchangesin the implementationof democracyin the management ofapublic schoolof Par is the overall goal. Theresearch isqualitative, with documentary analysis and questionnaires followed asemistructured script.In thetheoreticalpartis theassumption that thedemocratic management of theschoolreflectsthe democratic processof societyin which it operates. Theprimarycategoriesanalyzedare democracy, democratic managementand participation.Studies onthe concepts ofdemocratic managementand participationaxesconsistof the theoretical. The management modelrevealed byanalysis ofProgest oconveys theconcept ofmanagement fromaformal perspective, due topublic managementactionsthat adoptsflexible, participatory and decentralizedmanagementtranslated intomanagementas a factor inimproving the quality ofeducation.Instudiesof thebooksProgest o moduleswaspossible to recognizeaformal conceptionof democracy, serving as a support forconventionalmanagement practicesthat apparentlytakes thedemocratic discourse, but thatis notexercisedat the schoolobserved State SchoolCaraj s. In themanagement planState SchoolCaraj sisprovenreproductionof ideasof democracy, democratic management, participation by Progest odisseminated. It was found thatthe school communityperceives thedemocracy, democratic management, participation andresults-oriented. It is concludedthat theProgest ointroducesamanagement modelforpublic schoolmanagement.